Hubungan Dukungan Keluarga Dengan Kepatuhan Pengobatan Pasien Tuberkulosis Di Poli Paru RSUD Kota Tanjungpinang - Sugeng Rahayu; Elvi Murniasih; Fitriani Suangga (Jurnal Ilmiah Kedokteran dan Kesehatan, 2024)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis. India is ranked 3rd with the highest number of TB sufferers in the world after India and China. Globally, it is estimated that 9.9 million people suffer from TB in 2020. The total number of TB cases that have been discovered and treated (Treatment Coverage) in the Riau Islands Province in 2021 is 5,055 cases. This study aims to determine the relationship between family support and treatment compliance in Tuberculosis patients at the Pulmonary Polyclinic, Tanjungpinang City Hospital. This research design is descriptive quantitative with a cross sectional approach. A sample of 46 respondents was selected using the Purposive Sampling sampling technique. Data were processed using the Chi-Square test. Univariate data was obtained for the variable "High" Family Support of 87% and "Low" Family Support of 13%. For the "high" medication compliance variable it was 80.4% and "low" medication compliance was 19.6%. Bivariate analysis results show that there is a relationship between family support and treatment compliance with a p value of 0.000 (< 0.005). There is a relationship between family support and treatment compliance in Tuberculosis patients at the Pulmonary Polyclinic at Tanjungpinang City Hospital. In this research, nursing services can provide counseling or psychosocial support to families of Tuberculosis patients who still have a low level of compliance.